Utilization of Probiotics Among Dental Students: A KAP Study - Tejaswi Kala; Priyaranjan; Shilpa Sunil Khanna; Harveen Kaur; Nidhi Gupta; Anshuman Shetty; Heena Dixit Tiwari (Wolters Kluwer Medknow Publications, 2024)
Aim: The aim of the study is to know about the awareness of probiotics among undergraduate dental students. Materials and Methods: We conducted cross-sectional research where we had distributed a questionnaire consisting of ten open-ended questions, among 150 dental students through emails. The questions were based on the utilization of probiotics in dentistry. The data obtained was statistically analyzed with the help of Chi-square test. Results: In our study, we noted that most of the participants were aware of the term probiotics and had general ideas but were not fully aware of its pathogenesis. Around 83.2% of the participants were aware of probiotics and general concepts. We also noted that only 42.5% of the students agreed that probiotics can be used in the management of halitosis as well as periodontitis. Conclusion: We concluded that most of the dental students had a lack of awareness as well as were not familiar with the usage of probiotics in dentistry.